Informatividade na escrita argumentativa de terceiranistas do ensino médio noturno – um trabalho de autogerenciamento pautado pela pesquisa-ação - Arnemann, Aline Rubiane (2017)
This research, developed in classroom, with night shift high school third graders from a school that belongs to the educational public system run by the state and is located at the city of Santa Maria, RS, from August to December 2015, the objectives were: to contribute to the advance of night shift high school third graders’ argumentative writing using the informativeness criterion; to promote night shift high school third graders’ self-managing in relation to their textual production using a Textual Production Diary that functions as a game that places students as evaluators at their writing process and to contribute to teaching-learning process of argumentative writing through research-action. To achieve such objectives, the theoretical framework of this study is based on the socio interactionist teaching perspective, represented by Vygotsky (1991), from Text Linguistics, mainly, with Beaugrande and Dressler (1981), Val (1994), Bentes (2008), Marcuschi (2008), Fávero and Koch (2012), Koch (2014) and Koch and Elias (2014), from Information Science, represented by Capurro and Hjorland (2007) and from the perspective of textual genres from Dolz and Schneuwly (2004). The methodological framework is based on the research-action methodology, represented by Thiollent (2011), Carr and Kemis (1988) and Burns (1999). As teachers resources, the Freirean problematizing dialogism, Freire (2001, 2002, 2007), Freire and Faundez (1985) and Gadotti, Freire and Guimarães (2006) and the didactic sequence proposal from Dolz, Noverraz and Schneuwly (2004) were used. From the triangulation of the theoretical and methodological frameworks and the difficulties presented by learners concerning argumentative writing, we elaborated the categories of analysis of the present study. Such categories are guided by the informativeness degrees (low, medium and high), according to the articulation made from Beaugrande and Dressler (1981) and Val (1994) concerning the informativeness degrees, from Cunha (2001) concerning information sources and from Perelman and Olbrechts-Tyteca (2014) in relation to argumentation placement. Through such categories, streamlined and instrumented in the Textual Production Diary, students self-manage their learning process of textual production at both stages of writing and rewriting. The analysis of this research subject’s textual productions (S7) revealed that he promoted the advance of informativeness degree in his texts. In the first textual production, S7 presented low informativeness degree, in the last one he advanced to high informativeness degree. The analysis of the Textual Production Diary revealed that it serves as mediator instrument that helps the student self-manage his teaching-learning process. Therefore, we affirm that the categories of the analysis we propose contribute to the informativeness degree classification of texts and that self-managing, favored by the Textual Production Diary use, promoted the advance of informativeness degree of textual productions and of S7’s argumentative ability.